New methods of maintenance of freshwater snails for schistosome infections in the laboratory - Agrawal, M C (The Indian Journal of Animal Sciences, 2012)
A new method of keeping freshwater snails (Lymnaea luteola and Indoplanorbis exustus ) in the polythene bags with addition of mulberry leaves and stored water @ 50 ml/snail was developed. This facilitated easy transport of the snails, individual observations, and caused reduced mortality. There was no need of daily change of water. In another technique, a cement tank of 2.50 m diameter and 0.325 m depth was constructed with a water inlet in the centre. It was filled with mud, water, aquatic weeds including water lily, Hyacintilus, Vallisneria and wild snails of both the species. The tank was able to sustain life of both the snails and their breeding. The method was used to infect L. luteola with positive pig faeces and recovering Schistosoma incognitum cercariae in large number after about 30 days. These methods will be of great assistance in survey work and to search snail hosts in unknown life cycles .